Upaya Meningkatkan Hasil Belajar Peserta Didik dengan Menggunakan Model Mind Mapping (Peta Pikiran) dan Bantuan Media Audio Visual pada Mata Pelajaran IPA di Kelas III SDN 3 Langkai Palangkaraya - Rizki Handayani Majid; Muhamad Ramli (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
This study aims to determine the increase in learning outcomes and learning activities of Class III SDN 3 Langkai Palangkaraya students in science learning by applying the Mind Mapping Model and assisted by audiovisual media. The type of research used in the research is class action research (CAR) which seeks to solve or answer the problems faced in the current situation. The subject of this study amounted to 24 male students 13 and women 11. Data collection techniques used were observation and tests. Techniques for analyzing qualitative and quantitative data. The results of the study concluded that the learning activities of students in science learning by applying the Mind Mapping model and assisted by Audio Visual media of class III students in SDN-3 began to obtain an average score of 77.91 with good criteria. The pre-test results with an average value of 54.79 with classical completeness (8.33%) and the results of the first cycle obtained an average score of 77.91 with classical completeness (83.33%). Cycle II obtained an average value of 85 with classical completeness (100%).